SMART FARMING TECHNOLOGIES: TRANSFORMING AGRICULTURE THROUGH IOT AND AI - Asiya Akbar; Safia Gul; Tahira Bibi; Bibi Ilmas; Umar Khayyam (Spectrum of Engineering Sciences, 2025)
Smart farming combines Internet of Things (IoT) and Artificial Intelligence (AI) into agriculture and presents many new solutions to problems that traditional farming practices. The research was conducted at the Islamia University of Bahawalpur by the Department of Artificial Intelligence to evaluate the role of smart farming technologies in improving wheat production. The soil moisture, temperature, and environmental conditions were monitored using IoT-based sensors. Artificial intelligence algorithms are designed to make real-time analysis and decision-making. Automated irrigation, drone surveillance, and predictive disease detection systems were installed to compare with their traditional methods over a full cropping season. Results indicated that wheat yield achieved an increase of 23% while water consumption was reduced by 40%, input costs were brought down by 20%, improved crop health management was observed, and labor was reduced by 25%, thus increasing environmental sustainability through optimized resource use. Network stability and initial setup costs were minor setbacks, but farmers overwhelmingly commented positively on the systems, indicating a very bright prospective adoption scenario. The conclusion drawn from this study is that smart farming technologies enhance productivity, sustainability, and efficiency in agriculture. With proper infrastructural support, education, and funding, the IoT- and AI-based smart farming systems can play a significant role in the modernization of agriculture in Pakistan and similar developing regions, thus aiding long-term food security and environmental conservation.